Exploratory study of full-service restaurant industry in Singapore from retail perspective - Pang, Kok Chiang (2008)
The primary purpose of this study is to explore the full-service restaurant industry in Singapore by analyzing the retail strategies adopted by the restaurateurs in the face of intense competition in a dynamic business environment.